3D facial soft tissue changes after rapid maxillary expansion on primary teeth: A randomized clinical trial. (21st June 2018) - Fastuca, R.; Campobasso, A.; Zecca, P. A.; Caprioglio, A.
Structured Abstract: Objectives: The aim of the present randomized controlled trial (RCT) was therefore the tridimensional evaluation of soft tissue changes after rapid maxillary expansion in growing patients. Setting and Sample Population: Treated group comprised 17 patients (10 males and 7 females) with a mean age of 9.8 ± 1.2 years, and control group comprised 17 patients (13 males and 4 females) with a mean age of 9.1 ± 2.1 years. Material & Methods: All patients of the treated group underwent maxillary expansion with Haas‐type expander while patients of the control group underwent no treatment. 3D facial scans were acquired at T1, at the beginning of treatment or observation period, and at T2, 18 months apart. The mean interval between the timepoints was 18.2 ± 0.4 months. Results: The main differences between groups were reported in the nasal area. Nasal width (Alr‐All) significantly increased in the treated group compared with the control. The increase in intereye and mouth width in the study group did not show differences with the control group. No significant differences were reported for lips' protrusion, angular measurements and facial heights between groups. The total nose volume difference was significantly higher in the treated group compared with control, and this result was related mainly to the significant increase in the nasal dorsum volume. Conclusion: Maxillary expansion produced significant increase in the nasal base and nasal volumes, but its clinical relevance is still questionable.